(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aims and objectives: This prospective study aims to analyze foreign bodies in a term of a type, site, age, gender of distribution, and method of removal. Methodology: The presence of foreign bodies in the ENT is one of the most common causes of otorhinolaryngologic emergencies. Adults and children both present with foreign body lodgment in the ENT region. The symptoms may range from asymptomatic complaints to life-threatening conditions. This study compromises cases ranging from infants to the elderly population for a period from September 2020 to July 2021. The foreign body may classify as animate and inanimate The inanimate can be further classified as hydrophilic or hydrophobic and metallic or nonmetallic. The nonmetallic is classified as vegetative and nonvegetative. Results: The study shows a detailed analysis of foreign bodies in a term such as a type, size, age, gender, and removal in a comparison with a pre-pandemic period. Conclusion: We conclude that as compared with the pre-pandemic period it shows there is an increase in the incidence of foreign bodies in otorhinolaryngology during the pandemic in both adults and children. BACKGROUND: A foreign body is any object in a region it is not meant to be, where it can cause harm by its mere presence if immediate medical attention is not sought. It can be commonly found in the ear, nose, and throat. The presence of foreign bodies in the ENT region is one of the most common causes of otorhinolaryngologic emergencies.